Exploring technology acceptance across countries: case of mobile services adoption in the USA and Turkey. Issue 2 (19th March 2010) - Phan, Kenny; Daim, Tugrul; Basoglu, Nuri; Kargin, Banu
Mobile telecommunication industry is no longer relying on voice services. Recently, mobile services are gaining more popularity among the providers and their customers in the USA. US mobile telecommunication industry is also starting to rely more on mobile services. This paper presents two parts of a comprehensive research project undertaken: exploration of adoption factors in the USA and comparison of them with those found in Turkey in a prior study by the same research team. As the identified factors are integrated into the technology acceptance model (TAM), a new framework is outlined. This framework is expected to help the mobile service providers to design better mobile services that can address the needs of their users in different markets. The research methodology used in this study is a qualitative one. Interviews were conducted to justify the factors. The interview questions are designed specifically to address the factors related to mobile services. The interview results indicate that intermediary aspects (ease of use and usefulness) are the top aspects followed by service and social aspects. The results also showed that there were several similarities as well as some differences between the factors that affect the adoption of mobile services in the USA and Turkey.